PENGEMBANGAN MEDIA PEMBELAJARAN BIOLOGI VIRTUAL BERBASIS WEB BERNUANSA SCIENTIFIC LEARNING - Trisnawati Sarumaha (TUNAS : Jurnal Pendidikan Biologi, 2023)
This research is aimed to develope the teaching media by web-based through scientific learning which is able increase the student motivation and the result of student study. This research is Research and Development by using 4D development method. This research is experimented to the student 10th class in SMA Negeri 1 Telukdalam consist of 20 students. To standardize the product, it is done through three steps of test, consist of: test of validity, test of pratical, and test of efectivity. The research instrument is assessment questionnaire and evaluation test to find out the result of students study. The research output show that, this teaching media is valid with 95,725% and appropriate to be implemented. The average of pratical value by teachers 3,7 and students 3,8 in practically category. The students motivation result is 92,25% with cognitive average 88,7 compared before media implementation with average 58,8. Based on this research result concluded that teaching media of virtual biology by web-based through scientific learning is able to increase the motivation and result of student study additionally, as a valid, practical, and effective teaching media.